Village Baseline Study: Site Analysis Report for Kaffrine – Kaffrine, Senegal - Goudou D; Traoré Gue, J.N.; Ouédraogo, Mathieu; Segda, Zénabou; Badiane Ndour, Ndèye Yacine; Sall, Moussa; Gueye F; Sissoko, Keffing; Zougmoré, Robert B.; Moussa, Abdoulaye S. (2012)
The village baseline study of Toune Mosquée village in the CCAFS benchmark site Kaffrine in Senegal took place from June 2 to 4, 2011. Natural resources in the village are in a progressive state of degradation. The ‘protected’ forest has almost disappeared, the soils have low fertility and are degraded, and crop production is not sufficient to meet the food needs of a family throughout the year. Families must buy food to fill the gap in production. For that they harvest and sell forest products, which creates a vicious cycle of resource degradation. The male and female groups identified 35 organisations operating in the village including informal groups, state services, associations, NGOs and Muslim brotherhoods. While 18 of those work on food security issues, only 4 are involved in the management and protection of natural resources. Very few agricultural extension and training opportunities target women despite the women’s significant role in agriculture and livestock production. Women obtain information on livestock feeding techniques from people and organisations such as the horticultural project, women’s associations, and water and forest services. Men get information on soil inputs and soil fertility management from other farmers, organisations, radio and television, and from community leaders, notably the office of the village chief and the mosque on Fridays. The radio is the form of media most commonly used by the women but few women own a radio.